Outcomes Associated With Common and Immigrant-Group-Specific Responses to Intimate Terrorism. (February 2015) - Yingling, Julie; Morash, Merry; Song, Juyoung
The research for this article used available qualitative data from separate studies of South Asian-, Vietnamese-, and Hispanic-origin women victimized by intimate terrorism. Regardless of country of origin, period, or U.S. community, women used similar ways to cope. Consistent with perpetrators' misogynistic attitudes and aim of enforcing patriarchal expectations, many women responded to abuse from positions of powerlessness and fear. Instrumental help from family and friends and, depending on the group, advocacy agencies or counseling services assisted women in leaving men or stopping the abuse. Women used multiple coping strategies, often adding new approaches when those used initially failed.